Methods of improving the reconstructed image in systems with coded apertures - Никуляк, Александр Анатольевич (Eastern-European Journal of Enterprise Technologies, 2012)
The application of systems with a coded aperture to obtain tomographic information has its pros and cons. The advantages of such systems are the high sensitivity and noise-immunity (compared, for example, with tomographs on the basis of gamma-cameras), the ability to focus on a given surface within the object, etc. The drawbacks include the near-field artifacts, which occur during the decoding of the source position and depend on the choice of a coding mask and geometric parameters of the system. In addition, the quality of the restored image is affected by the accuracy of the formation of the matrix of countability. The article studies the impact of the interaction of gamma-radiation with a substance on the quality of the formation of the matrix of countability and, as a result, on the quality of the restored image. It describes the method of formation of the correcting processing array and its use as a way to improve the restored image